Binaural Pitch Fusion: Effects of Amplitude Modulation. (July 2018) - Oh, Yonghee; Reiss, Lina A. J.
Hearing-impaired adults, including both cochlear implant and bilateral hearing aid (HA) users, often exhibit broad binaural pitch fusion, meaning that they fuse dichotically presented tones with large pitch differences between ears. The current study was designed to investigate how binaural pitch fusion can be influenced by amplitude modulation (AM) of the stimuli and whether effects differ with hearing loss. Fusion ranges, the frequency ranges over which binaural pitch fusion occurs, were measured in both normal-hearing (NH) listeners and HA users with various coherent AM rates (2, 4, and 8 Hz); AM depths (20%, 40%, 60%, 80%, and 100%); and interaural AM phase and AM rate differences. The averaged results show that coherent AM increased binaural pitch fusion ranges to about 2 to 4 times wider than those in the unmodulated condition in both NH and bilateral HA subjects. Even shallow temporal envelope fluctuations (20% AM depth) significantly increased fusion ranges in all three coherent AM rate conditions. Incoherent AM introduced through interaural differences in AM phase or AM rate led to smaller increases in binaural pitch fusion range compared with those observed with coherent AM. Significant differences between groups were observed only in the coherent AM conditions. The influence of AM cues on binaural pitch fusion shows that binaural fusion is mediated in part by central processes involved in auditory grouping.